2016
DOI: 10.2337/db16-0287
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interleukin-32 Levels in Obesity Promote Adipose Tissue Inflammation and Extracellular Matrix Remodeling: Effect of Weight Loss

Abstract: Interleukin (IL)-32 is a recently described cytokine involved in the regulation of inflammation. We aimed to explore whether IL-32 could function as an inflammatory and angiogenic factor in human obesity and obesity-associated type 2 diabetes. Samples obtained from 90 subjects were used in the study. Obese patients exhibited higher expression levels of IL-32 in visceral adipose tissue (AT) as well as in subcutaneous AT and peripheral blood mononuclear cells. IL32 was mainly expressed by stromovascular fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 44 publications
(56 reference statements)
1
35
0
1
Order By: Relevance
“…IL‐32 exerts important roles in the pathogenesis of infectious, autoimmune and inflammatory diseases . Increased IL‐32 expression has been found in VAT from patients with obesity promoting inflammation and ECM remodelling and contributing to the development of obesity‐associated comorbidities . Reportedly, the increased circulating levels of IL‐32 in human obesity and obesity‐associated T2D decrease after weight loss .…”
Section: Adipose Tissue Inflammation and Dysregulated Adipokine Profimentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐32 exerts important roles in the pathogenesis of infectious, autoimmune and inflammatory diseases . Increased IL‐32 expression has been found in VAT from patients with obesity promoting inflammation and ECM remodelling and contributing to the development of obesity‐associated comorbidities . Reportedly, the increased circulating levels of IL‐32 in human obesity and obesity‐associated T2D decrease after weight loss .…”
Section: Adipose Tissue Inflammation and Dysregulated Adipokine Profimentioning
confidence: 99%
“…136 Reportedly, the increased circulating levels of IL-32 in human obesity and obesity-associated T2D decrease after weight loss. 136 Previous studies have demonstrated that inflammatory cytokines such as IL-1β, interferon (IFN)-γ or TNF-α induce the expression of IL-32 and, in turn, IL-32 also stimulates IL-8, IL-6, IL-1β and TNF-α production, constituting a classical proinflammatory mediator with relevant functions in angiogenesis, ECM remodelling and apoptosis (Figure 3). In this sense, a potential involvement of IL-32 in the development of obesity-associated colon cancer as a proinflammatory and ECM remodelling cytokine has been proposed.…”
Section: F I G U R Ementioning
confidence: 99%
“…Obesity is associated with increased IL-32 levels, and these are reduced following bariatric surgery 251 . This cytokine may represents a therapeutic target and warrants further study.…”
Section: Therapeutic Implications Of Macrophage Biologymentioning
confidence: 99%
“…RNA (2 µg) were reverse transcribed to cDNA according to standard procedures [26]. The mRNA levels for adiponectin (ADIPOQ), collagen (COL)-1A1, COL6A3, decorin (DCN), elastin (ELN), IL1B, IL6, IL8, IL18, kruppel-like factor 4 (KLF4), matrix metalloproteinase (MMP)-2, MMP9, TGFB1, tumour necrosis factor-α (TNF) and tenomodulin (TNMD) were quantified by Real-Time PCR (7300 Real Time PCR System, Applied Biosystems, Foster City, CA, USA) as previously described [26]. Primers and probes (Merck, Darmstadt, Germany) were designed using the software Primer Express 2.0 (Applied Biosystems, Foster City, CA, USA) ( Supplementary Table S1).…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…Primers and probes (Merck, Darmstadt, Germany) were designed using the software Primer Express 2.0 (Applied Biosystems, Foster City, CA, USA) ( Supplementary Table S1). The cDNA was amplified as previously described [26]. The endogenous control gene 18S rRNA (Applied Biosystems) was the endogenous control for Real-Time PCR experiments and a relative quantification was obtained using the ∆∆Ct formula.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%